2000
DOI: 10.1039/b001452o
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive stripping voltammetric determination of ketoconazole in pharmaceutical preparations and urine using carbon paste electrodes

Abstract: The oxidation of ketoconazole on a bare carbon paste electrode was studied voltammetrically. The results indicated that the process is irreversible and controlled by an adsorption-extraction process which allows the accumulation of the drug at the electrode surface. After the optimization of solution pH, accumulation variables and instrumental parameters, sensitive differential pulse and linear sweep voltammetric peaks were obtained whose peak currents were linearly proportional to the ketoconazole concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…[9][10][11][12] In this work, we initially studied the reaction between clotrimazole (CT) (a drug containing an imidazole ring) and triiodide ions. We found that the protonated clotrimazole (CTH + ) is precipitated in the presence of excess I3 -ions as a (CTH)I3 ion pair.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] In this work, we initially studied the reaction between clotrimazole (CT) (a drug containing an imidazole ring) and triiodide ions. We found that the protonated clotrimazole (CTH + ) is precipitated in the presence of excess I3 -ions as a (CTH)I3 ion pair.…”
Section: 8mentioning
confidence: 99%
“…7,8 We recently studied the electrochemical behavior and some chemical properties of various antifungal drugs containing piperazine or imidazole groups such as, ketoconazole in aqueous and non-aqueous media. [9][10][11][12] In this work, we initially studied the reaction between clotrimazole (CT) (a drug containing an imidazole ring) and triiodide ions. We found that the protonated clotrimazole (CTH + ) is precipitated in the presence of excess I3 -ions as a (CTH)I3 ion pair.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shamsipur et al [16] developed a triiodide PVC membrane sensor based on a charge-transfer complex of I 2 with 2,4,6,8-tetraazabicyclo [3.3.0] octane and used it as an indicator electrode in potentiometric titration of triiodide ions. We have recently studied the electrochemical behavior and some chemical reactions of ketoconazole (KC) (an antifungal drug) in aqueous and non-aqueous media [17,18]. Also, we have found that the protonated KC (as dication) is precipitated in the presence of I À 3 ions as (KCH 2 )(I 3 ) 2 ion pair.…”
Section: Introductionmentioning
confidence: 99%
“…Ketoconzole has been titrated potentiometrically using perchloric acid as titrant [5]. Several different articles have been published for the determination of ketoconazole spectrophotometrically [23][24][25] , Voltametrically [26], by HPTLC [27], by HPLC [23,28,29] and by LC-MS [30]. The USP [13] Use mobile phase consists of diisopropylamine in methanol (7:3) conducted through C18 column.…”
Section: Column and Mobile Phasementioning
confidence: 99%